The Nexus of Experience and Job Performance: A Qualitative Research at SMAN 1 Krian Sidoarjo - Arianti, Eva (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aimed to analyze the impact of teaching experience on the work performance of pre-service teachers at SMAN 1 Krian Sidoarjo, utilizing qualitative research methods and case study techniques involving observation, document analysis, and interviews. The study, conducted in November 2022, focused on understanding human behavior in a post-positivist framework, using the researcher as the main instrument for data collection and inductive/qualitative data analysis. The findings underscored the pivotal role of teaching experience in enhancing the competence and performance of pre-service teachers. Factors such as management support, collaborative efforts among teachers, and reflection on teaching experiences emerged as crucial indicators of success. This research contributes valuable insights to the development of pre-service teacher professional development programs. Teaching experience was revealed as not only shaping the teacher's role in the classroom but also serving as a foundation for developing professional identity and mentorship skills for students. The challenges faced during the learning process contributed to dynamic and strengthened understanding. Reflecting on teaching experiences became a fundamental practice, fostering continuous improvement in teaching methods. School management support, breaking down structural barriers, and fostering a supportive work environment were identified as crucial elements in professional growth. This study significantly contributes to understanding how teaching experience positively influences pre-service teachers' job performance.